PENGARUH PERMAINAN HURUF PUNGGUNG BERANTAI TERHADAP KEMAMPUAN MENULIS HURUF HIJAIYAH ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Deswita Linda Sofia; Wusono Indarto; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: based on the results of field observation to the ability to write letters hijaiyah students is still low and teacher still use learning methods that dominate and not varied. So that should be the application of the chain letters back play. This study aims to determine the effectiveness of the application of the chain letters back play to the ability to write letters hijaiyah children ages 5-6 years in TK Negeri Pembina 3 Pekanbaru. The sample used in this study 15 people. The data collection techniques were used that observation. Data were analyzed using t-test. The study hypothesis was the ability to write letters hijaiyah child after applying backs chain letter game also shows the results of analysis of data obtained t = 16.412 and p = 0.000 because p <0.05, it can be concluded that there are differences in the ability to write letters hijaiyah children very significant protege after using the chain letters back play. So it means that Ho is rejected and Ha accepted which means there is a very significant difference between before and after the experiment by applying the chain letters back play. And also on the hypothesis test can be seen t = 16.412> t table = 2.145. Thus Ho rejected and Ha accepted.Keywords: Ability Write, the chain letters back